PENYAJIAN MAKANAN MASYARAKAT DI DAERAH ALIRAN SUNGAI SIAK DESA TUALANG KECAMATAN TUALANG KABUPATEN SIAK - Elsa Riani; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Indonesian people, consisting of various ethnicities and occupying different areas of residence, have developed a very diverse diet. The difference in food serving is related to the potential in each region that causes differences in behavior in response to nature. People in the watershed of life can not be separated from the river, the river as a source of life both bathing, washing, as well as food sources such as fish. So that in terms of food people in consuming what food is always eat fish from the catch. The problem formulation is how food is served (preparation, processing, and presentation) in the watershed of Tualang Village Siak Regency. The study subjects were 8 people who lived in the watershed for 10 years, in determining the subject of the author using purposive sampling techniques. Data collection is carried out using observation, interview, and documentation methods. The results of this study show that in terms of food the community ranging from preparation, processing, and presentation does not fully process the fish caught depending on the catch gained and the public buys more often in the market for a few weeks. The situation and conditions faced by fishermen are caused by their low education, factor of old age, difficulty finding work, ability and expertise are very lacking. Norms and values that fishermen believe are the norms that fishermen believe are the rules they agreed without writing and as fishermen must also know that taking fish as necessary. Keywords: Food Serving, Watershed Communities